Effect of tea extract (Camellia sinensis) on shelf life and intrinsic quality of tempe - Astawan, Made; Prayudani, Ayu P G; Hadiningtias, Primanisa; Wresdiyati, Tutik; Andi Early Febrinda (Hasanuddin University Food Science and Technology Study Program, 2024)
Tempe is Indonesian traditional food made from fermented soybeans. Tempe has a short shelf life due to its high moisture content and the activity of microorganisms. The shelf life of tempe can be increased by using tea extract in tempe processing because tea contains antioxidant and antimicrobial components. This research aims to evaluate the effect of using tea extract in tempe processing on the shelf life, physicochemical characteristics, and sensory profile of tempe. During storage, the shelf-life test used the descriptive observation method on the colour, flavour, taste, and texture. The use of 0.5% black tea extract in the initial soaking of soybeans can increase the shelf life of tempe to 4 and 6 days at room and refrigerator temperature, respectively. The result showed that tempe had significantly (p<0.05) lower ash content (0.81% wb), brightness (65.37), and pH (6.50), while the texture (15.3 Kg force) was significantly higher (p<0.05) than the control (untreated tempe). The results of sensory evaluation using the hedonic rating test showed that fresh tempe with black tea extract treatment had significantly lower (p<0.05) colour, texture, and overall attributes than the control one. The same evaluation on fried tempe showed that the black tea extract treatment significantly increased (p<0.05) the texture attribute compared to the control.